Development of a skill acquisition periodisation framework for high-performance sport - Farrow, D.; Robertson, S. (Sports Medicine, 2017)
Unlike physical training, skill acquisition does not currently utilise periodisation to plan, monitor and evaluate programs. Development of a skill acquisition periodisation framework would allow for systematic investigation into the acute and longitudinal effectiveness of such interventions. Using the physical training literature as a reference point, a skill-training periodisation framework was developed for use in high-performance sport. Previous research undertaken in skill acquisition was used to provide support for the framework. The specificity, progression, overload, reversibility and tedium (SPORT) acronym was adopted. Each principle was then re-conceptualised so that it related to relevant skill acquisition principles. Methods for the measurement and analysis of each principle are provided and future directions for the longitudinal assessment of skill acquisition are discussed. The skill acquisition periodisation framework proposed in this study represents an opportunity for the principles relating to skill acquisition training to be measured in a systematic and holistic manner. This can also allow for a more sophisticated evaluation of the efficacy of longitudinal training programmes and interventions designed for sustained skill enhancement